2010
DOI: 10.1016/j.pmrj.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Nerve Entrapment Syndromes in Veterans With Lower Limb Amputations

Abstract: A high number of veterans with lower limb amputations presented with upper limb nerve entrapment syndromes. Careful attention to these nerve entrapment syndromes in lower limb amputees is necessary because the symptoms may be confounded by other chronic pain-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Similarly these muscles are also very important for proper trunk control and positioning in a wheelchair. As the upper limbs must be used for successful transfers (e.g., from a bed, commode, or wheelchair), special attention must also be focused on strengthening the patient’s triceps, pectoral, and latissimus muscles, as well as with teaching proper transfer techniques to preserve upper limb function and avoid injuries to the shoulder, elbow, or wrist, because the risk of overuse and entrapment nerve injuries are greater for amputee and wheelchair user populations [89]. When necessary, special equipment such as a sliding board may be indicated.…”
Section: Rehabilitation Strategies For Individuals With Multiple Limbmentioning
confidence: 99%
“…Similarly these muscles are also very important for proper trunk control and positioning in a wheelchair. As the upper limbs must be used for successful transfers (e.g., from a bed, commode, or wheelchair), special attention must also be focused on strengthening the patient’s triceps, pectoral, and latissimus muscles, as well as with teaching proper transfer techniques to preserve upper limb function and avoid injuries to the shoulder, elbow, or wrist, because the risk of overuse and entrapment nerve injuries are greater for amputee and wheelchair user populations [89]. When necessary, special equipment such as a sliding board may be indicated.…”
Section: Rehabilitation Strategies For Individuals With Multiple Limbmentioning
confidence: 99%
“…This is the first study to investigate the prevalence of Ulnar Neuropathy at the elbow and ulnar nerve dislocation in wheelchair marathon athletes. The prevalence of Ulnar Neuropathy in wheelchair marathon athletes was 28.9%, which was higher than in able-bodied persons but lower than reported in other populations with lower limb dysfunction [7,14,15]. In addition, the prevalence was comparable to that reported in wheelchair athletes engaging in track racing and intermittent team sports [22,23].…”
Section: Discussionmentioning
confidence: 78%
“…wheelchair racing, the elbow maximumly flexes from 168 to 180˚at 14mph [28]. While these factors may theoretically place wheelchair athletes at a further heightened risk for Ulnar Neuropathy compared with non-athletic wheelchair users, the prevalence of Ulnar Neuropathy in wheelchair marathon athletes was lower than found in non-athletes with lower limb dysfunction [7,14,15]. The lower prevalence of Ulnar Neuropathy in the wheelchair athletes in the present and other studies [22,23] compared with non-athlete populations with lower limb deficiencies [14,15] suggests that engaging in regular exercise may provide some protection against the development of Ulnar Neuropathy.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence and intensity of shoulder pain in these studies involving Veterans were not associated with the age of the Veteran and only moderately associated with the duration of wheelchair use. Another study found that 80 percent of Veterans with lower-limb amputations had median neuropathy across both wrists, and 70 percent had ulnar nerve entrapment across elbows that was attributed to the improper fit of assistive devices and overuse injuries [16]. With the onset of pain or injury, wheelchair users may begin to withdraw from community participation, become dependent on others, functionally decline, and require more medical care and expenditures [2,5].…”
Section: Introductionmentioning
confidence: 99%